The possible contexts of inclusion and special educational needs in the light of an international research - Fónai, Mihály; Barnucz, Nóra; Hüse, Lajos (Acta Medicinae et Sociologica, 2021)
The relationship between school integration and special educational needs (hereinafter: SEN) is analyzed in the framework of an international resarch in this study. In the theoretical part the process of segregation, integration and inclusion is introduced, and also the use of the concepts is dicussed. The integration in the school system means the approach and practice against segregated education of students with disabilities with the aim to eliminate segregated education. SEN is not a diagnostic but an educational concept, and the its special pedagogy and legal term do not coincide. The research was extended to Ukrainian (the Transcarparthian n=280), Polish (n=271) and Hungarian students (n=552). The results show that school inclusion and social support are increased by school success. Success can increase the self-esteem of students with learning problems, which co-occures with the subjective perception of increasing social support and decreasing exclusion.